Practical Issues Concerning Temporary Carbon Credits in the CDM - Michael Dutschke; Bernhard Schlamadinger (Hamburg Institute of International Economics (HWWA), 2003)
Afforestation and reforestation (AR) projects in the Clean Development Mechanism are able to create emission permits that can be accounted against the industrialized countries' commitments for limiting their greenhouse gas emissions, as agreed under the Kyoto Protocol. The discussion of how to treat credits from temporary carbon stocks is centering on the proposal for expiring emission credits from AR, which in the subsequent commitment period need to be replaced. While the basic methodological question is thus being solved, the practicalities arising from the solution have so far not been considered. The authors make new proposals on accounting modalities, define the tCER value as compared to a permanent CER, and forecast who will be the potential buyers for temporary offsets.
Keywords: Q13; Q23; Q25; 330; Clean Development Mechanism; Forestry; Klimaschutz; Internationale Umweltpolitik; Aufforstung; Umweltzertifikat; Zeit; Kohlendioxid; Welt